Analysis of Teachers’ Questions in The EFL Classroom at Junior High School in Padang - Uswatun Hasanah Yude; Yetti Zainil (Journal of English Language Teaching, 2021)
In EFL context mostly, teachers pose questions to check students’ understanding and stimulate students’ curiosity. There are many types of questions that can be asked by teachers. Each question gives a different influence on students’ thinking levels. This research was intended to analyze the most types of questions asked by teachers in EFL classroom activity in SMPN Kota Padang. This research is descriptive research. It involved observing and describing the behaviour of a subject, also using the written data from Geschool without influencing it in any way. The subjects of this research were 18 teachers from 6 schools selected by using random sampling technique. The techniques of data collection were classroom observation-video recordings and written questions from Geschool. The findings of this research are the most type of questions asked by teachers in EFL classroom activity in SMPN Kota Padang is the common level of questions asked by teachers in EFL classroom activity in SMAN Kota Padang is remembering (C1) category, with 155 questions (40,15 % of the total questions) which is the lowest level of thinking in cognitive domain.